2020
DOI: 10.3329/kyamcj.v10i4.45714
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Pain, Physical Function and Radiography With Osteoarthritis of The knee

Abstract: Background: Osteoarthritis (OA) of the knee is a major public health issue. It is important to have a clear understanding about the relationship between clinical features (Pain, functional impairment) and radiographic findings to select appropriate treatment option. Objectives: To investigate the relationship between pain, loss of physical function, and radiographic findings in OA of the knee joint. Materials and Methods: A cross sectional study on 90 patients aged 40 years and above with OA of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Emerging evidence from Bangladesh reported a high prevalence of osteoarthritis and related illnesses among the older population in Bangladesh [14][15][16][17][18]. One study reported that 12.1% of adults aged 60 and above have symptomatic knee osteoarthritis, and the prevalence of osteoarthritis in rural and urban slum and affluent urban communities are 7.5%, 9.2%, and 10.6%, respectively [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emerging evidence from Bangladesh reported a high prevalence of osteoarthritis and related illnesses among the older population in Bangladesh [14][15][16][17][18]. One study reported that 12.1% of adults aged 60 and above have symptomatic knee osteoarthritis, and the prevalence of osteoarthritis in rural and urban slum and affluent urban communities are 7.5%, 9.2%, and 10.6%, respectively [15].…”
Section: Introductionmentioning
confidence: 99%
“…Emerging evidence from Bangladesh reported a high prevalence of osteoarthritis and related illnesses among the older population in Bangladesh [14][15][16][17][18]. One study reported that 12.1% of adults aged 60 and above have symptomatic knee osteoarthritis, and the prevalence of osteoarthritis in rural and urban slum and affluent urban communities are 7.5%, 9.2%, and 10.6%, respectively [15]. Findings from the first national survey related to musculoskeletal conditions and related disabilities in Bangladeshi adults show that 30.4% of adults in Bangladesh have musculoskeletal conditions, 7.3% have knee arthritis, and among the adults with musculoskeletal conditions, 24.4% have some form of disabilities [14].…”
Section: Introductionmentioning
confidence: 99%
“…Studies carried out in Bangladesh have shown the similar results. 8,10 This similarity in BMI may be explained by perhaps similar ethnicity and socioeconomic condition of two countries.…”
Section: Discussionmentioning
confidence: 88%